Business interdependence, factor of quality management – a peruvian fishing industry Business case - Paredes Tarazona, Mildred (2001)
The generation of interdependence relationships is studied centered in factors psychosocials: Motivation, Perception and Interests that propitiate business shared in a representative sample of the sector managerial exporter fishing Peruvian. The analysis of data with statistical non pamétricos points out that the studied variables are not very significant to conform strategic alliances in the perspective of the sustainable development.